Deadly crush - Day, Maddie (Day, Maddie. Cece Barton mystery., 2024)
"After a mostly stress-free Christmas with her college-age daughter, and despite enjoying a current budding romance with fellow newcomer, Benjamin Cohen, it's time for Cece to focus on Vino y Vida, the Colinas wine bar she manages. Electrical work and an outdoor security camera are needed, and she's hired local electrician Karl Meier to do the job, along with the help of his nephew Ian. But she regrets her choice when she witnesses Karl needlessy berating Ian in her presence. On top of that, Karl leers at her, then presents her with an inflated bill before the work is complete. Still, she's shocked when she gets a call from Karl's ex-wife, Josie, that she's found Karl . . . crushed to death beneath the lift in her automotive shop. Cece convinces Josie to call the police, even though Josie is terrified. After all, Karl was an abusive husband, was threatening her, and she has no alibi. With Josie's future on the line, and maybe her own, Cece starts her own investigation. From the customers Karl cheated to the other women he harassed, she finds there's no lack of suspects-other than the shelter kittens to whom he was an uncharacteristically sweet volunteer. With a bouquet of motives and unanswered questions, Cece is going to need the help of her twin, Allie, who owns a nearby B & B, as she dives into Karl's past-before the killer catches up with her, and the lights go out for good . . ."--